Perbandingan Performans Dua Strain Broiler Yang Mengonsumsi Air Kunyit - Tantalo, Syahrio (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The objective of the research was to know comparation of two strains of  broiler performance which were consumed with kunyit water.  Level of water kunyit as treatment was 10 g/600 ml.  Two strains of broiler were CP 707 unsexed and Lohmann unsexed. Every broiler strain consist of 100 Day Old Chicken (DOC).    Experiment  was  designed  with  two  treatments  of  strain  broiler  and  each  treatment  had  15 replications. Each replication was 6 or 7 DOC. Comparison of data was analyzed by using  t student on 5%  signification    (Steel  dan  Torrie,  1993).  Parameters  measured  were  water  consumption,  feed  intake, body weight gain, feed conversion, and income over feed cost. Results showed the highest effect of kunyit water  significant  (P<0,05)  of  broiler  performance  of  strain  CP  707  on  water  consumption,  feed  intake, and body weight gain, but no significant effect on feed conversion, and income over feed cost. Broiler of strain  CP 707 was the responsive to treated water kunyit of consumption which shown on its effect on performance.